2006
DOI: 10.1016/j.difgeo.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

On variational approach to differential invariants of rank two distributions

Abstract: In the present paper we construct differential invariants for generic rank 2 vector distributions on n-dimensional manifold. In the case n = 5 (the first case containing functional parameters) E. Cartan found in 1910 the covariant fourth-order tensor invariant for such distributions, using his "reduction-prolongation" procedure (see [12]). After Cartan's work the following questions remained open: first the geometric reason for existence of Cartan's tensor was not clear; secondly it was not clear how to genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 18 publications
0
67
0
4
Order By: Relevance
“…• We note here a theorem of Cartan that the vanishing of A i 's is actually a necessary and sufficient condition for all Weyl tensorC of the respective radii r 1 and r 2 ) rolling on each other 'without slipping or twisting' has been investigated for a while during recent years, see [1,4,5,17]. It is therefore well known that the distribution D v defined by such a system on the configuration space C(S 2 r1 , S 2 r2 ) is integrable if and only if the radii r 1 and r 2 of the balls, are equal.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…• We note here a theorem of Cartan that the vanishing of A i 's is actually a necessary and sufficient condition for all Weyl tensorC of the respective radii r 1 and r 2 ) rolling on each other 'without slipping or twisting' has been investigated for a while during recent years, see [1,4,5,17]. It is therefore well known that the distribution D v defined by such a system on the configuration space C(S 2 r1 , S 2 r2 ) is integrable if and only if the radii r 1 and r 2 of the balls, are equal.…”
Section: 1mentioning
confidence: 99%
“…Montgomery/I. Zelenko, [5,17], says that if, in addition to r 1 = r 2 , the ratio of the radii is r 1 : r 2 = 3 or r 1 : r 2 = 1 3 , then the (2, 3, 5) distribution D v has the maximal local symmetry in the non-integrable case, in which case the local symmetry group is G 2 . This remarkable observation gives a 'physical' realization of this exceptional Lie group; a realization unnoticed by mathematicians and physicists for more than 100 years, from the year 1894, when E. Cartan and F. Engel, have shown that this group is a symmetry group of a certain rank two distribution in dimension five [8,10].…”
Section: 1mentioning
confidence: 99%
“…This family includes appropriate complexifications of the rolling distributions of two real surfaces of different nonzero constant curvature whose curvatures do not have ratio 9:1; for that ratio the rolling distribution is flat. See [1,7,8,10,32] for much more. -(Section 51) There is a single distribution with infinitesimal symmetry algebra isomorphic to so(3, C)⊕(so(2, C) C 2 ).…”
Section: Cartan's Ostensible Classificationmentioning
confidence: 99%
“…Of course, these nice things have some value only if we can effectively find Jacobi curves for singular extremals: their definition was too abstract. Fortunately, this is not so hard; see [5] for the explicit expression of Jacobi curves for a wide class of singular extremals and, in particular, for singular curves of rank 2 vector distributions (these last Jacobi curves have found important applications in the geometry of distributions, see [11,14]). …”
Section: Monotonicitymentioning
confidence: 99%